KECIRIAN PERIODE MUTA’AKHIRIN PERSPEKTIF ASH-SHIDDIQIE DALAM PENULISAN SEJARAH HADIS: KAJIAN HISTORIOGRAFI HADIS - Samsir (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
This study aims to determine the development of hadith from time to time based on a particular figure, namely Muhammad Hasbie ash Shiddiqie who only focuses on the muta'akhkhirin period starting from the fourth century onwards. There are two questions raised in this research, namely: First, what is the history of hadith writing during the muta'akhirin period and its methodology in the view of Muhammad Hasbi ash-shiddiqie? Second, how was the intellectual contribution of the scholars during the muta'akhirin period and what books emerged during the muta'akhirin period? The method of this research is a qualitative method with the type of literature study using a historiographic approach. So that in this research it can be seen the results that during the muta'akhkhirin period many hadith books were born as well as a large number of hadith figures found in each time.